Lev Gets "Anthology of Riflemen's Art": history and artistic features of the Ukrainian Sich Riflemen’s handmade book-album - Hakh Iryna (Рукописна та книжкова спадщина України, 2023)

(untitled)
The goal of the work. Representation of the handmade book-album "Anthology of Riflemen's Art" (1915-1917) - an epoch-making work of verbal, musical and artistic culture of the beginning of the 20th century, created during the First World War by 27 military of the Ukrainian Sich Riflemen. For more than a hundred years, the “Anthology..." was kept in the Vallicelliana Library in Rome, awaiting publication in 2021. The history of the creation and subsequent fate of the book-album is closely related to the life of its creator - the artist-compiler Lev-Osyp Gets. The research methodology consists in the application of the historical and cultural approach to the historical, artistic and bibliographic analysis of the artistic and figurative problems of the handmade book-album. Scientific novelty. For the first time, an attempt has been made to conduct a historical-artistic analysis of a single handmade book-album of the beginning of the 20th century as a valuable source of understanding the cultural context of the First World War period. Conclusions. The proposed study is the first attempt at a systematic examination of the historical, cultural and aesthetic meanings of the found art album "Anthology of Riflemen's Art" and an artistic analysis of the graphic images of Lev Gets, a famous Ukrainian-Polish artist of the 20th century. All the illustrative and textual information presented for the first time deepens the historical-documentary and pictorial-artistic facts of the life and creative activity of not only L. Gets, but also of individual personalities of 26 Ukrainian Sich Riflemen: artists, poets, musicians, and serves as convincing evidence of the creation of an expressive visual and written culture of the Ukrainian Legion of 1915-1917. The unique works of the authors of all the artistic material presented in the album make it possible to realize and properly assess the cultural significance of the creative heritage of Ukrainian Sich Riflemen artists. The painting content of the "Anthology..." is based on a high level of expertise and represents expressive national-semantic and spiritual-aesthetic values.